Comparison of Childhood Traumatic Experience and Attachment Styles among Patients in Suicide Attempts with Drugs and the Healthy Control Group - Sinay Onen; Ahmet Inel; Bilgen Bicer Kanat; Ibrahim Taymur; Ersin Budak; Suna Eraybay (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Aim: Early traumatic experiences and neglect can be related to negative emotional, cognitive and neurodevelopmental changes and can lead to a predisposition to several mental disorders, including suicidal behaviors. In this study we aimed to examine the attachment styles of suicide attempters using drugs and their early traumatic experiences, compared to healthy controls. Method: The study involved 76 people who had attempted suicide with drugs and 84 healthy controls who did not have any psychiatric disorder. In the evaluation we have used the following: a sociodemographic data form, Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Childhood Traumas Questionnaire (CTQ - 28) and Relationship Scales Questionnaire (RSQ) with those who agreed to participate in the study. Results: Fearful attachment styles from the relation scale survey of those who attempted suicide were significantly higher than the control group (p [JCBPR 2017; 6(2.000): 51-58]